Analysis Of The Production Process And Marketing Strategy For Pasteurized Milk Jelly At Rumah Babe, An Sme In Bengkulu City - Putri Sabrina (Jurnal Multidisiplin, 2026)
The milk processing industry based on micro, small, and medium enterprises (MSMEs) plays an important role in increasing the added value of livestock products while meeting the community’s demand for healthy and nutritious food. This study aims to analyze the production process and marketing strategies of pasteurized jelly milk at Rumah Babe MSME in Bengkulu City. The research was conducted from November to December 2025 using a qualitative descriptive method through direct observation, interviews, and documentation studies. The results showed that the production process of pasteurized milk at Rumah Babe was carried out systematically, starting from raw material inspection, pasteurization, cooling, addition of supplementary ingredients, packaging, to product labeling. Quality control was implemented through specific gravity testing, alcohol testing, pH testing, and organoleptic testing to maintain the quality of fresh milk. The marketing strategy applied was multichannel-based, including direct marketing to consumers, consignment systems in bakeries and local supermarkets, and digital marketing through social media platforms such as WhatsApp, Instagram, and Facebook. Product distribution was conducted using cooler boxes to maintain product quality during delivery. This integrated marketing strategy was able to expand market reach and improve the competitiveness of local dairy products in Bengkulu City. The study indicates that the combination of hygienic production processes and modern marketing strategies is an important factor in the development of dairy-processing MSMEs.